2015
DOI: 10.1186/s40691-015-0048-3
|View full text |Cite
|
Sign up to set email alerts
|

Overweight boy’s and girl’s experiences with and perception of athletic clothing and its relationship to physical activity participation

Abstract: The purpose of this study was to explore the relationship between athletic clothing and physical activity in overweight children. The perceptions of athletic clothing among overweight children were also investigated. The researchers asked: (a) what are overweight children’s experiences with athletic clothing, (b) does clothing impact overweight children’s motivation to participate in physical activity, and (c) are there differences between boys and girls? Focus groups and individual interviews were conducted w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…behavior. Even in activities peripherally related to exercising, such as purchasing athletic wear, thin bodies are glorified and centered as the norm(Reddy-Best & Harmon, 2015). Hypothesis 2 will argue that fat phobia negatively reinforces exercise by incentivizing the creation of real or perceived distance between one's body with a fat body; however(e.g., pride) that are most relevant in reinforcing exercise.Biological underpinnings of exercise rewardsInvestigations into measuring endocannabinoid release during exercise could be compared against self-report measures of postexercise positive affect (i.e., including while exercise intensity is manipulated) to explain whether the exercise rewards described in this hypothesis are more salient at a biological level (i.e., if exercise elicits elevated endocannabinoids in individuals with AN) or a cognitive level (i.e., if no differences in AN vs. non-AN are observed, which could indicate that the rewards are not biologically based but rather cognitively perceived).…”
mentioning
confidence: 99%
“…behavior. Even in activities peripherally related to exercising, such as purchasing athletic wear, thin bodies are glorified and centered as the norm(Reddy-Best & Harmon, 2015). Hypothesis 2 will argue that fat phobia negatively reinforces exercise by incentivizing the creation of real or perceived distance between one's body with a fat body; however(e.g., pride) that are most relevant in reinforcing exercise.Biological underpinnings of exercise rewardsInvestigations into measuring endocannabinoid release during exercise could be compared against self-report measures of postexercise positive affect (i.e., including while exercise intensity is manipulated) to explain whether the exercise rewards described in this hypothesis are more salient at a biological level (i.e., if exercise elicits elevated endocannabinoids in individuals with AN) or a cognitive level (i.e., if no differences in AN vs. non-AN are observed, which could indicate that the rewards are not biologically based but rather cognitively perceived).…”
mentioning
confidence: 99%
“…In addition, parents concerned for their child’s weight identified decreasing clothing size as a strong motivator for positive health behaviour change, and this was consistent with a previous study that found that older children self-reported a motivation to lose weight to have clothes fit better to improve looks (Lambert- et al, 2016). Children with overweight and obesity may have more difficulty finding fashionable clothing that fits well and provides adequate coverage (Brock et al, 2010), and inability to dress in a manner and style typical to peers may increase the risk of children experiencing social exclusion and bullying by their peers (Reddy-Best and Harmon, 2015). Parents concerned for their child’s food choices identified improving food choices, decreasing BMI and decreasing clothing size as significant motivators for positive health behaviour change, while difficulty being consistent about home health changes was a significant barrier to change.…”
Section: Discussionmentioning
confidence: 99%
“…For example, women report the need for a longer inseam on pants and shorts to accommodate for larger thighs (Christel et al, 2016). Exercise apparel fit is an issue identified by overweight youth (Reddy-Best & Harmon, 2015) as well as adults who wear plus-size clothing (Christel & O’Donnell, 2016).…”
Section: Studymentioning
confidence: 99%